Efficacy and Safety of a Switch to Rilpivirine-Based Regimens in Treatment-Experienced HIV-1-Infected Patients: A Cohort Study. Issue 4 (May 2016) - Gazaignes, Sandrine; Resche-Rigon, Matthieu; Gatey, Caroline; Yang, Chloe; Denis, Blandine; Fonsart, Julien; Desseaux, Kristell; Guionie, Michel; Rozenbaum, Willy; Delaugerre, Constance; Molina, Jean-Michel
Background: Rilpivirine (RPV) is a second-generation once-daily non-nucleoside reverse transcriptase inhibitor (NNRTI) which has shown non-inferior antiviral activity to efavirenz in treatment-naive patients. Data in treatment-experienced patients are more limited. We wished to assess the efficacy and safety of a switch to RPV-based regimens in well-suppressed treatment-experienced patients. Methods: Between September 2012 and June 2013, all antiretroviral therapy (ART)-experienced HIV-1-infected patients with a plasma HIV RNA level <50 copies/ml, and switching to an RPV-based regimen, were analysed in this retrospective observational monocentric cohort study. The primary end point was the proportion of patients with virological success defined as a plasma HIV RNA level <50 copies/ml at 12 months using the FDA snapshot algorithm. Results: A total of 281 participants were studied and 97% received a combination of RPV/tenofovir disoproxil fumarate/emtricitabine. At month 12, the rate of virological success was 59% and increased to 72% using available data beyond month 12. Sixteen (6%) patients experienced virological failure, which was associated with the presence of the M184V/I resistance mutation in prior genotypes ( P =0.02) and the use of a non-NNRTI as third agent before the switch ( P =0.03). RPV-based regimens were overall well tolerated and only 23 (8%) patients discontinued ART because of adverse events, mostly neuropsychiatric adverse events. Switching to RPV was associated with significant but modest improvement of the lipid profile. Conclusions: In patients fully suppressed on ART, a switch to an RPV-based regimen should only be considered in the absence of prior virological failure or resistance mutations to nucleoside reverse transcriptase inhibitors and NNRTIs to avoid virological failures.